Vaccine strategies against schistosomiasis - A. Capron; J. P. Dessaint; M. Capron; R. J. Pierce (Memorias do Instituto Oswaldo Cruz, 1992)
In this review the authors analyze the effector and regulatory mechanisms in the immune response to schistosomiasis. To study these mechanisms two animal models were used, mouse and rat. The mouse totaly permissive host like human, show prominent-T cell control in the acquisition of resistance. But other mechanisms like antibody mediated cytotoxity (ADCC) involving eosinophils and IgG antibodies described in humans, are observed in rats. Also in this animal, it is observed specific IgE antibody high production and blood and tisssue eosinophilia. Using the rat model and schistosomula as target, some ADCC features have emerged: the cellular population involved are bone marrow derived inflammatory cell (mononuclear phagocytes, eosinophils and platelets), interacting with IgE through IgE Fc receptors. Immunization has been attempted using the recombinant protein Sm28/GST. Protection has been observed in rodents with significant decrease of parasite fecundity and egg viability affecting the number, size and volume of liver egg granulomas. The association of praziquantel and immunization with with Sm28/GST increases the resistance to infection and decreases egg viability. The authors suggest the possibility of the stablishment of a future vaccine against Schistosoma mansoni.